Comparação do tratamento com bota de unna e o curativo convencional em pacientes com anemia falciforme e úlceras em membros inferiores ensaio clínico controlado randomizado - Barroso, Nathalia Vasconcelos (2015)
The ulcers of the lower limbs are cited as the main cutaneous manifestation of sickle cell anemia, presenting a chronic course, with pain and many complications. Treatment of sickle ulcers is complex, involving care wound bed, management of anemia, pain management and treatment of opportunistic infections, among the various proposed treatments highlight the use of covers with inelastic bandage impregnated with zinc, the boot Unna. However there are still no controlled trials to prove the efficacy of treatment. Objective: Compare treatment with conventional dressing to the use of Unna boot in patients with sickle cell anemia and ulcers in the limbs. Methodology: This is a randomized clinical trial, which analyzed patients with sickle cell ulcers that took the Unna boot , comparing them with patients with sickle cell ulcers who used the conventional dressing . Treatments were performed in a period of six weeks. Statistically analyzed the areas of lesions in three periods: at baseline (D0) in the third week (D3) and the sixth week (D6). Results: Participated in this study 19 patients with a mean age of 35.9 years (95% CI 29.1 to 42.8), 53% (10/19) were male. In these individuals was analyzed the healing of ulcers in 40 lower limbs of people with sickle cell anemia 57% (23/40) in the experimental group and 43% (17/40) in the control group. There was a mean variation in lesion area when used Unna boot of 20.2 cm2 at T0 time, 17.9 cm2 in time T3 and 6.2 cm2 in time T6 (P < 0.001), mean percentage of total reduction of 77 1%, obtained by Tarajad index, when used as a simple dressing ranged from 31.3 cm2 35.8 cm2 33.9 cm2 at times T0, T3 and T6, respectively (P <0.001) and an average percentage of 22.8 %. Conclusion: The results suggest that the use compression therapy with Unna boot is an effective treatment of lower limb ulcers in patients with sickle cell anemia, aimed at reducing ulcer area, improvement of the injury aspect and pain alleviation.